2021
DOI: 10.1016/j.msec.2020.111784
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic heating as a new tool for protein scaffold engineering

Abstract: Ohmic heating (OH) is recognised as an emerging processing technology which recently is gaining increasing attention due to its ability to induce and control protein functionality. In this study, OH was used for the first time in the production of scaffolds for tissue engineering. BSA/casein solutions were processed by OH, promoting protein denaturation and aggregation, followed by cold-gelation through the addition of Ca 2+ . The formation of stable scaffolds was mostly dependent on the temperature and treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…These changes can induce the aggregation of proteins and affect protein digestibility by compromising the efficacy of digestive enzymes and production and the release of digestive end products [ 125 ]. Similarly, ohmic heating, which applies the Joule effect to produce heat inside the food products through the application of alternating current [ 126 ], affects the structure of proteins and their interactions and the formation of protein aggregates [ 127 ]. The conformational, structural, and microstructural changes induced in the food proteins and matrices during ohmic heating are a result of a combined effect of thermal and non-thermal effects (electrochemical reactions and electrical effects) [ 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes can induce the aggregation of proteins and affect protein digestibility by compromising the efficacy of digestive enzymes and production and the release of digestive end products [ 125 ]. Similarly, ohmic heating, which applies the Joule effect to produce heat inside the food products through the application of alternating current [ 126 ], affects the structure of proteins and their interactions and the formation of protein aggregates [ 127 ]. The conformational, structural, and microstructural changes induced in the food proteins and matrices during ohmic heating are a result of a combined effect of thermal and non-thermal effects (electrochemical reactions and electrical effects) [ 127 , 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, ohmic heating, which applies the Joule effect to produce heat inside the food products through the application of alternating current [ 126 ], affects the structure of proteins and their interactions and the formation of protein aggregates [ 127 ]. The conformational, structural, and microstructural changes induced in the food proteins and matrices during ohmic heating are a result of a combined effect of thermal and non-thermal effects (electrochemical reactions and electrical effects) [ 127 , 128 ]. Ohmic heating has been reported to increase the digestibility of whey proteins by unfolding their complex structure by disrupting the covalent bonds and, thereby, increasing the availability of hydrolytic sites [ 129 ].…”
Section: Resultsmentioning
confidence: 99%
“…Scaffolds for tissue engineering can be produced using BSA (4.19%, w/v) and casein (0.69%, w/v) through the Ca 2+ -induced "cold gelation" procedure [93]. A recent study unveiled that a proper optimization of the heating conditions during the scaffolds' production can avoid the use of reducing agents such as ditiotreitol (DTT) [4]. Figure 2 evidence microstructure of BSA/casein scaffold produced under conventional heating and ohmic heating, highlighting the importance of the heating process and presence of an electric field on the obtainment of singular protein networks.…”
Section: Milk-derived Proteinsmentioning
confidence: 99%
“…Another study showed that, independent of the level of protein purification, the extracts from A. platensis can help stabilize emulsions; however, authors also conclude that purification can improve functionality by yielding smaller emulsion droplets and stronger viscoelastic networks at the oil-water interface [103]. Contrary to what happens to common animal-based proteins such as milk, proteins from microalgae biomass can act as emulsions and foams stabilizers in a broad range of pH and ionic strength due to their characteristically low isoelectric point (3)(4) [97].…”
Section: Microalgae Proteinsmentioning
confidence: 99%
See 1 more Smart Citation